Planteamiento para establecer un medio de comunicación y difundir masivamente la fundación Soluciones Juveniles, por medio de una emisora online. (2018)
The importance of being able to be in the current market requires fast and effective modern means that can have a massive reach for the target audience according to the service offered or for the brand to be positioned. For this reason it was necessary to conduct an investigation through surveys and interviews with students, graduates, employees and directors' team of the Youth Solutions Foundation at Christ For The Nations Institute in Colombia, in order to demonstrate the need for an online Radio station to disseminate all their productions, which until now had not been done. After executing a pilot test, we observed the satisfaction of the community's response to this proposal and the desire to stay connected with what concerns the Institute's life.